Black and green : black insights for the green movement - Ali, Jamal (Jamal M.) (Hamilton Books, 2009)
This book is a call to action for the Black community to join the green movement. The book offers insights, ideas, and strategies that demonstrate how Black people can benefit from and fuel the go-green effort.